Life values structure in a Spanish sample of adolescents - Tejerina-Arreal, Maria; Garcia-Gomez, Pilar; Garcia-Guardia, Maria L. (Anales de Psicología / Annals of Psychology, 2014)
We examined the structure of personal life values as a representation of underlying motivation, in a Spanish sample of children and adolescents 12 - 16 years old. In general, results showed that youth put higher priority on intrinsic life goals (meaningful relationships, being physically healthy, self-acceptance) than extrinsic life goals (image, money, power). Gender differences were found in specific life goals. When comparing our results with another longitudinal American study using the same instrument and methodology, we found similar results, although Spanish youth value priorities goals related to support rather than striving as in American adolescents. Cultural and age trend in life priorities are discussed.